2020
DOI: 10.1016/j.jbi.2020.103601
|View full text |Cite
|
Sign up to set email alerts
|

Defining facets of social distancing during the COVID-19 pandemic: Twitter analysis

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 23 publications
(26 reference statements)
1
31
0
Order By: Relevance
“…The term social distancing is a relatively older concept; however, its enactment has seen variations with the changing times. Early studies of the preventive measure of social distancing found that it is a multi-faceted intervention where facets or stages unfold as the pandemic impacts society (Kwon et al, 2020). These facets may change in subsequent studies as deeper insights into COVID 19 evolves.…”
Section: Preventive Measures and Covid 19mentioning
confidence: 99%
“…The term social distancing is a relatively older concept; however, its enactment has seen variations with the changing times. Early studies of the preventive measure of social distancing found that it is a multi-faceted intervention where facets or stages unfold as the pandemic impacts society (Kwon et al, 2020). These facets may change in subsequent studies as deeper insights into COVID 19 evolves.…”
Section: Preventive Measures and Covid 19mentioning
confidence: 99%
“…Themes of previous studies that focus on exploration of, description of, correlation of, or predictive modeling with Twitter data during COVID-19 pandemic include sentiment analysis [17], [25], [26], [27], [28], public attitude/interest measurement [21], [29], [30], [31], content analysis [32], [33], [15], [34], [35], [36], topic modeling [37], [16], [38], [39], [40], [26], [27], analysis of misinformation, disinformation, or conspiracies [41], [20], [42], [43], [44], [45], [46], outbreak detection or disease nowcasting/forecasting [19], [18], and more [47], [48], [49], [50], [51], [52]. Similarly, data from other social media channels (e.g.…”
Section: Going Beyond Correlationsmentioning
confidence: 99%
“…One of the challenging issues during the COVID-19 pandemic around the world is spreading information and misinformation. Many reviewed articles mentioned this significant issue in outbreaks and other natural disasters (Smith 2010;Doan et al 2011;Sreenivasan et al 2011;Thomson et al 2012;Cho et al 2013;Carter 2014;Kostkova et al 2014;Oyeyemi et al 2014;Cooper et al 2015;Takahashi et al 2015;Fu et al 2016;Mukkamala and Beck 2016;Wang et al 2016;Chatfield and Reddick 2017;Ortiz-Martínez and Jiménez-Arcia 2017;Subba and Bui 2017;Ahmed et al 2018;Ferrara 2020;Golder et al 2020;Kouzy et al 2020;Kwon et al 2020;Rosenberg et al 2020;Rufai and Bunce 2020;Sarker et al 2020;Sharma et al 2020;Wicke and Bolognesi 2020;Yang et al 2020). It was claimed that publishing misinformation about the COVID-19 pandemic has reached alarming levels that endanger public health (Kouzy et al 2020).…”
Section: Disseminating Informationmentioning
confidence: 99%
“…Rapid assessment during the first days after a natural disaster and during the response is vital to improve operations. Some of the reviewed articles mentioned this significant topic as a function of Twitter in natural disasters (Smith 2010;Fu et al 2016;Ahmed et al 2018;Golder et al 2020;Kwon et al 2020;Sarker et al 2020;Wicke and Bolognesi 2020). For example, Sarker et al (2020) found that Twitter data on the characteristics of people infected with COVID-19 were as useful as clinical data (Sarker et al 2020).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation